Glaucoma Intraocular Pressure and Aqueous Dynamics - Ichhpujani, Parul (IntechOpen, 2016)
Written for ophthalmology residents and practitioners, this book provides the most comprehensive resource covering all the major aspects of aqueous humor and intraocular pressure dynamics. In addition to chapters on the conventional and new technologies for intraocular pressure assessment, there is a novel chapter on the engineering perspectives of continuous monitoring of the intraocular pressure. Based on the newer insights in aqueous outflow, this text offers a rational approach to the medical and surgical management of glaucoma.